Real-time synthesis and detection of plasmonic metal (Au, Ag) nanoparticles under monochromatic X-ray nano-tomography - Bharti, Amardeep; Chae, Keun Hwa; Goyal, Navdeep (Nature Publishing Group, 2020)
Plasmonic nanostructures are of immense interest of research due to its widespread applications in microelectronics, photonics, and biotechnology, because of its size and shape-dependent localized surface plasmon resonance response. The great efforts have been constructed by physicists, chemists, and material scientists to deliver optimized reaction protocol to tailor the size and shape of nanostructures. Real-time characterization emerges out as a versatile tool in perspective to the optimization of synthesis parameters. Moreover, in the past decades, radiation-induced reduction of metallic-salt to nanoparticles dominates over the conventional direct chemical reduction process which overcomes the production of secondary products and yields ultra-high quality and pure nanostructures. Here we show, the real-time/in-situ synthesis and detection of plasmonic (Au andAg) nanoparticles using single synchrotron monochromatic 6.7 keV X-rays based Nano-Tomography beamline. The real-time X-ray nano-tomography of plasmonic nanostructures has been first-time successfully achieved at such a low-energy that would be leading to the possibility of these experiments at laboratory-based sources. In-situ optical imaging confirms the radiolysis of water molecule resulting in the production of e(aq)(-)OH(center dot), and O-2(-) under X-ray irradiation. The obtained particle-size and size-distribution by X-ray tomography are in good agreement to TEM results. The effect of different chemical environment media on the particle-size has also been studied. This work provides the protocol to precisely control the size of nanostructures and to synthesize the ultrahigh-purity grade monodisperse nanoparticles that would definitely enhance the phase-contrast in cancer bio-imaging and plasmonic photovoltaic application.